’n Herwaardering van aanhouding sonder verhoor in die lig van die Bybelse beskouing van menseregte - Botha, C. J. (Koers, 1981)
Human rights in general and detention without trial in particular have been discussed with great fervour in the course of the past few years. Because this is in teality a normative issue, writers have tended to approach the matter from the viewpoint of Humanism and Natural Law, while in the process neglecting to keep cognizance of a Biblical view o f human rights.